Intra-articular injection of platelet lysate-derived extracellular vesicles recovers from knee osteoarthritis in an in vivo rat model - Maria Antònia Forteza-Genestra; Miquel Antich-Rosselló; Carmen Ráez-Meseguer; Anna Tomàs Sangenís; Javier Calvo; Antoni Gayà; Marta Monjo; Joana Maria Ramis (Journal of Orthopaedic Translation, 2024)
Objective: MSCs and Platelet-Rich Plasma are the main focus in the study of new regenerative treatments aimed to reverse Osteoarthritis (OA). However, extracellular vesicles (EVs) present several advantages to cell-based treatments. Thus, the aim of this study was to compare and evaluate the regenerative potential of MSC-derived EVs (cEVs) and platelet-derived EVs (pEVs) in an OA cartilage rat model. Design: OA in vivo model was established through injection of 6 mg MIA in the rat knee joints. After 14 and 21 days, OA knee joints were treated with 1 × 1010 particles of pEVs or cEVs. At day 28, the animals were sacrificed, plasma was collected to quantify CTX-II and knee joints were excised to be evaluated by Cone Beam Computed Tomography (CBCT). After decalcification, histology was used to determine the OARSI score and to visualize collagen and glycosaminoglycan content. Results: pEVs and cEVs samples did not show significant differences per se but they did in terms of regenerative effects on OA knee joints. pEVs-treated knee joints showed better subchondral bone integrity in CT-analysed parameters when compared to cEVs or OA group, showing similar values to the healthy control group. Moreover, OARSI score indicated that pEVs showed a greater OA reversion in knee joints, especially in female rats, and so indicated the analysed histological images. Conclusions: pEVs are proposed as a viable regeneration treatment for OA since they are not only capable of exerting their regenerative potential on osteoarthritic cartilage, but also outperform cEVs in terms of efficacy, particularly in females. Significance statement: Osteoarthritis (OA) is one of the most age-related diseases. It is estimated that 500 million people suffer from OA worldwide, representing the principal cause of chronic disability in adults. In the present study we evaluated the therapeutic effect of extracellular vesicles (EVs) from different sources (platelet lysate and human umbilical cord mesenchymal stromal cells) in an in vivo rat model. Our results demonstrate that platelet-derived EVs (pEVs) induce an OA reversion in knee joints, thus evidencing the therapeutic potential of pEVs as cell-free regenerative agents for OA treatment. The translational potential of this article: Platelet-derived extracellular vesicles (pEVs) offer a promising cell-free therapy option for OA treatment. Their production could be easily standardized and reproduced without extensive platelet harvesting and amplification, thus paving the way for their clinical translation.